Caribe - Ramírez, Esteban (Filmmaker); Istarú, Ana, 1960-; Perugorría, Jorge; Salazar Herrera, Carlos, 1906-1980 (Cinetel, 2004)
Vicente Vallejo chose the exuberant and multicultural Costa Rican Caribbean to forge his dream of living with his wife Abigail, by the sea. His only client, a transnational banana company, unexpectedly decides to terminate his contract due to the fluctuations of the market. His situation is further complicated by the surprise arrival of young Irene, his wife's half-sister, and the installation of an American oil company in the area, which divides the community between the need for new jobs and the fear of harm environmental. The pain and frustration lead Vicente to a borderline situation. Jackson, an old black fisherman, neighbor of the Vallejo, observes everything. In a crisis, Vicente will do everything possible so that his dreams do not collapse...--